STUDY OF CONVECTIVE FLOWS IN THREE-COMPONENT GAS MIXTURES BY THE METHOD OF NUMERICAL SIMULATION - Kossov В.Н.; Mukamedenkyzy В.; Z.Z З.З.; Khasseinova А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The characteristics of convective flows arising in three-component gas mixtures are investigated by the method of numerical simulation. The time variation of the isoconcentration lines of the heavy component of the mixture and the average velocity are considered as characteristics of convective flows. To calculate the characteristics of convective flows arising in a vertical cylindrical channel, we used a numerical model based on the splitting scheme according to physical parameters. It was shown that in three-component gas mixtures, where special diffusion regimes are manifested, non-monotonic distributions of component concentrations and velocities are possible. The time of loss of stability of mechanical equilibrium and the time of developed convective flows are determined.